2012
DOI: 10.1007/s00436-011-2808-3
|View full text |Cite
|
Sign up to set email alerts
|

Zoophilic feeding behaviour of phlebotomine sand flies in the endemic areas of cutaneous leishmaniasis of Sindh Province, Pakistan

Abstract: Leishmania (Leishmania) major has been identified as the major causative agent of cutaneous leishmaniasis in Sindh Province of southern Pakistan. To make a rational approach for understanding the pathogen transmission cycles, the sand fly species and their natural blood meals in the endemic areas were examined. Total DNA was individually extracted from sand flies collected in four villages in Sindh Province. PCR-RFLP (restriction fragment length polymorphism) and sequence analysis of the 18S ribosomal RNA gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 32 publications
0
9
0
2
Order By: Relevance
“…P. papatasi is semi-domestic species and opportunistic feeder but prefers to feed on human and rodents (Yaghoobi-Ershadi et al, 1995). Tiwananthaqorn et al (2012) reported that P. alexandri feeds on dogs, sheep and goats despite its anthropophilic behavior. Consistent with our findings, negative synanthropic index may be due to availability of hosts such as, dogs, sheep and goats in natural habitats in comparisons with the urban and semi urban areas of Khorramshahr.…”
Section: Discussionmentioning
confidence: 99%
“…P. papatasi is semi-domestic species and opportunistic feeder but prefers to feed on human and rodents (Yaghoobi-Ershadi et al, 1995). Tiwananthaqorn et al (2012) reported that P. alexandri feeds on dogs, sheep and goats despite its anthropophilic behavior. Consistent with our findings, negative synanthropic index may be due to availability of hosts such as, dogs, sheep and goats in natural habitats in comparisons with the urban and semi urban areas of Khorramshahr.…”
Section: Discussionmentioning
confidence: 99%
“…The patients resided in different villages and cities of Larkana, Shahdadkot and Dadu districts of Sindh province or part of Balochistan province (Figure 1) [15,16]. For 64 samples, the genomic DNA was extracted from amastigotes in skin biopsy specimens using GenomicPrepℱ cell and a tissue DNA Isolation Kit (Amersham Pharmacia Biotech, Piscataway, NJ, USA), according to the manufacturer’s instructions [15].…”
Section: Methodsmentioning
confidence: 99%
“… Map of Pakistan, showing the study area (figure is modified from  [16] . Pie charts show the proportion of each population sampled in the respective region.…”
Section: Methodsmentioning
confidence: 99%
“…Due to various limitations in the microscopic detection of Leishmania in sand flies, a molecular mass screening method for Leishmania infection of sand fly individuals has been established ( Kato et al 2007 , 2010 ). This method is a powerful tool for research confirmed on prevalent sand fly species and vector-host-parasite inter-relationships ( Kato et al 2007 , 2010 , Tiwananthagorn et al. 2012 ).…”
mentioning
confidence: 99%